2006
DOI: 10.3390/curroncol13030010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geometric Uncertainties on Dose Distribution During Intensity Modulated Radiotherapy of Head-and-neck Cancer: The Need for a Planning Target Volume and A Planning Organ-at-Risk Volume

Abstract: We assessed the effect of geometric uncertainties on target coverage and on dose to the organs at risk (OARS) during intensity-modulated radiotherapy (IMRT) for head-and-neck cancer, and we estimated the required margins for the planning target volume (PTV) and the planning organ-at-risk volume (PRV). For eight headand- neck cancer patients, we generated IMRT plans with localization uncertainty margins of 0 mm, 2.5 mm, and 5.0 mm. The beam intensities were then applied on repeat computed tomography (CT) scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A margin of 3 to 5 mm was added around the GTV and CTV to account for uncertainties in setup and organ motion and to obtain the planning target volume (PTV). We have previously reported that these margins are effective in preventing significant deviation from the prescribed dose in these patients 13 . The CT images and structure sets were then transferred to a commercially available inverse treatment planning system (CORVUS, V.5.0, NOMOS Corp) to generate IMRT plans.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A margin of 3 to 5 mm was added around the GTV and CTV to account for uncertainties in setup and organ motion and to obtain the planning target volume (PTV). We have previously reported that these margins are effective in preventing significant deviation from the prescribed dose in these patients 13 . The CT images and structure sets were then transferred to a commercially available inverse treatment planning system (CORVUS, V.5.0, NOMOS Corp) to generate IMRT plans.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that these margins are effective in preventing significant deviation from the prescribed dose in these patients. 13 The CT images and structure sets were then transferred to a commercially available inverse treatment planning system (CORVUS, V.5.0, NOMOS Corp) to generate IMRT plans.…”
Section: Radiotherapy Protocolmentioning
confidence: 99%
“…These modifications can be related to multiple factors, such as (1) shrinkage of large tumor and/or nodal masses; (2) weight loss; and (3) resolution of post-operative changes. Different studies have shown that the radiation dose to the target volume and organs at risk can vary significantly due to spatial and volume variability during treatment [ 6 , 7 ]; thus, the re-planning of treatment with adaptive radiotherapy may ensure adequate doses to the target volumes despite these anatomical changes [ 8 ]. Prospective trials are now evaluating the clinical benefit of adaptive radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Inter-fractional changes in patient anatomy constitute a significant source of error in external-beam radiotherapy. During the course of treatment, drastic changes in patient anatomy can occur due to weight loss (Müller et al (2015) found patients lost up to 12.8 kg over the course of a radiotherapy schedule), as well as tumor and surrounding tissue shrinkage (Ballivy et al 2006, Hansen et al 2006, Loo et al 2010, where (Barker et al 2004) showed head and neck (HN) tumors can shrink up to 69.5% over the course of treatment. Adaptive radiotherapy (ART) can reduce dosimetric errors linked to anatomical changes by re-optimizing treatment parameters based on patient anatomy of the day.…”
Section: Introductionmentioning
confidence: 99%